Intra-urban mobilities and the depiction of the city in Zimbabwean fiction as reflected in Valerie Tagwira’s uncertainty of Hope (2006) - Musanga, Terrence (Sage Publications, 2016)
This article explores intra-urban mobilities and the depiction of the city in contemporary Zimbabwean literature as reflected in Valerie Tagwira’s Uncertainty of Hope. It shall be argued that intra-urban mobilities are closely related to the depiction of the city as a heterogeneous space that is unevenly constituted. This unevenness is influenced by economic and political factors and translates into the realm of the social and symbolic as some spaces are projected as “safe” and “respectable” while others are conceptualized as of “ill repute” and “threat” to the security, morals, and safety of its inhabitants. However, the boundaries between “safe” and “threatening” spaces are constantly transgressed by Zimbabwean urban dwellers in their day to day struggles for survival in a harsh and unrelenting economic and political climate. This political and economic environment has resulted in most Zimbabweans being insecure as testified by heightened intra-urban mobilities. Furthermore, the insecurity and intra-urban mobility are exemplified by the creation of unstable identities premised on fear, anxiety, and restlessness that characterize the lives of most urban dwellers.